Collectivist and Individualist End-User Values in the Digital Energy Community Ecosystem - Tuomela, Sanna; Juntunen, Jouni K. (IEEE, 2024)
Energy community (EC) is an emerging entity in the energy system. EC information system enables energy consumers and prosumers collectively generate, use, share and trade renewable energy, as well as communicate and exchange data and information within the EC and with external stakeholders. End-user values collectivism and individualism are strongly related to the participation in the energy community through the information system. Collectivistic and individualistic value categories were elicited in 96 value-focused interviews with energy consumers and prosumers as potential energy community members. Although these value categories are partly conflicting, they disclose shared goals that may be implemented in the EC information system.
Keywords: energy community; user values; digital platform; fi=Markkinointi|en=Marketing|; fi=Tuotantotalous kaupp|en=Industrial Management econ|